Texturas gráficas en base al análisis morfológico de las máscaras de la diablada pillareña y su incidencia en la industria textil. - Paredes Díaz, Kevin Joel (2023)
The cultural manifestations have been an ancestral means of communication, where it can be identified that currently there is a lack of attention by people towards cultural festivities, so this research was to develop graphic textures based on the analysis of the morphology of the masks of the diablada Pillareña, which is a native character of the canton of Píllaro. It was seen in the need to encourage to know and give the value of cultural identity, looking for innovative solutions through graphic design. One of the objectives was to design graphic textures based on the analysis of the masks, in the same way to make compositions of textures and implement them in textiles. One of the methodologies implemented was field research, both with qualitative and quantitative approach, to obtain results through semi-structured questions, directed to an artisan of the canton. We also developed the methodology of Design Thinking in the generation of innovative ideas in the ideation of the modules of the graphic textures, through cards that helped us to the morphological analysis, which helped us to obtain shapes, colors. The modular compositions card allowed us to make the composition of modules. The prototype sheet helped us to visualize references of the final product, with the compositions previously made. In the validation, textile supports (mockups) were developed to obtain sets, whose names are based on the parishes of the Píllaro's cato. The project aims to contribute to the ancestral identity based on the morphological analysis of the masks of the devil of Píllaro, through the creation of modules of graphic textures, allowing the preservation of the ancestral traditions of the people.